Exploration of capability and role development in an emerging technology network. Issue 7 (5th October 2018) - Salehi, Fatemeh; Zolkiewski, Judith; Perks, Helen; Bahreini, Mohammad Ali
Abstract : Purpose: The purpose of this study is to investigate the capabilities and roles of three types of actors, specifically technology-based start-ups, incumbent firms and intermediaries, in co-constructing a network for development and commercialization of an emerging technology. In particular, the research aims to understand how the roles played by network actors evolve during the development and commercialization process and what operational and dynamic capabilities are developed by actors through collaboration. Design/methodology/approach: A single longitudinal case study methodology was applied to analyse roles and operational and dynamic capabilities developed in a network setting by multiple parties over time. Findings: The findings indicate that actors need to take on new roles to be successful when dealing with an emerging technology in a network context and they need to develop certain dynamic capabilities to enact these roles. The study categorizes roles and capabilities of network actors through various stages of collaboration. Actors developed sensing capabilities in the pre-collaboration stage which drove joint new product development. During the collaboration, seizing capabilities were developed where resource commitment and alignment of resources among actors were essential. Capabilities gained through commercialization and large-scale production were predominantly transforming capabilities where actors realigned their structure and had positive impact on capability development in the wider network. Research limitations/implications: Using data of a single case data may limit the applicability of the findings, which calls for future research. Practical implications: The findings inform managers'' and policymakers' strategies related to participation in networks for development and commercialization of emerging technologies. The research provides insights about the role of large and small firms as well as intermediary organizations in development of nanotechnology and highlights that all network actors need to develop and utilize dynamic capabilities in all areas of sensing, seizing and transforming over time to be able to innovate and successfully commercialize a new product. Originality/value: The research investigates evolution of operational and dynamic capabilities and roles of multiple actors over time in collaborative networks for development and commercialization of an emerging technology. Building on the dynamic capabilities concept, the study broadens our understanding of the evolution of these capabilities in a network setting and elaborates how capability development is linked to changes in roles.